The Effect of Rehabilitative Exercises Using Diverse Aquatic Modalities on Athletes with Rotator Cuff Tendinitis or Tears - Abd, Muhammad Thauban; Yaseen, Ali Mseer (Indonesian Journal Publisher, 2025)
The importance of this study stems from the premise that aquatic exercise can expedite recovery and improve the range of motion and functional strength of the injured shoulder through the use of in-water assistive implements—such as aquatic (foam) dumbbells, floatation boards, and hand paddles—while enhancing neuromuscular responsiveness in individuals with rotator cuff injuries. The study aimed (1) to design a set of rehabilitative exercises employing diverse modalities within an aquatic environment for athletes diagnosed with rotator cuff tendinitis or tears, and (2) to examine the effect of these aquatic rehabilitative exercises on this population. An experimental approach was used, employing a single-group pretest–posttest design appropriate to the study’s nature and objectives. The sample comprised six athletes from various sports who had clinically diagnosed rotator cuff tendinitis or tears. Field procedures included trials and tests to measure shoulder joint range of motion (ROM) in the following movements: flexion, extension, abduction, adduction, internal rotation, and external rotation; as well as muscular strength in the same planes (flexion, extension, abduction, adduction, internal rotation, and external rotation). Based on the results obtained, the researcher concluded that rehabilitative exercises utilizing diverse aquatic modalities have a positive effect on the rehabilitation outcomes of the study participants. The findings showed statistically significant differences between pre- and post-measurements for all ROM variables, indicating the effectiveness of the aquatic program in improving the ROM of the injured shoulder. Statistically significant improvements were also recorded in all shoulder muscular strength variables, suggesting that the in-water rehabilitative exercises substantially increased rotator cuff muscle strength in the injured athletes. The researcher recommends incorporating aquatic rehabilitative exercises using varied aquatic implements into return-to-function programs for athletes with rotator cuff injuries, given their clear and significant impact on ROM and muscular strength.